Optimization of parameter choice of information protection system - Браіловський, М. М.; Хорошко, В. О.; Хорошко, О. В. (Proceedings of National Aviation University (archive), 1999)
Considered is the choice critérium of quality index of complicated machine parameters. Proposed critérium allows to estimate the system in the scale of possible deviations of proper criteria and as the result to take into account additionally the degree of deterioration of one parameter at the expense of others